x/(120-x)=(60-x)/60
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 01:41:11
x/(120-x)=(60-x)/60x/(120-x)=(60-x)/60x/(120-x)=(60-x)/60两边都乘以60(120-x)(x≠120)60x=(60-x)(120-x)60x=7
x/(120-x)=(60-x)/60
x/(120-x)=(60-x)/60
x/(120-x)=(60-x)/60
两边都乘以 60(120-x) (x≠120)
60x=(60-x)(120-x)
60x=7200-180x+x²
x²-240x+7200=0
(x-120)²=14400-7200
=7200
x-120=±√7200=±60√2
x=120±60√2
x/(120-x)=(60-x)/60
x/(120-x)=x/60
120+60%x=x
x(x-1)(x+1)=60
60%X + 80%X - 12 = X
60x(x-4)=30x
7x-3x+x=60
x-(25%x+6)=60%x
x - (x - 120)*60%-120=1/4x
60+3x=120+2x x=?
(x+60)x(1+10%)-(1-20%)x=120
(60-x)(120-x)=800x是多少
(120-X)/(60-X)=40%,x等于多少
x+2/3x=60 x-3/5x=120 4x+18x=1x+2/3x=60 x-3/5x=120 4x+18x=132!
x+3分之2 x=60 x-5分之3x=120 4x+18x=132x+3分之2 x=60 x-5分之3x=120 4x+18x=132
x+2/3x=60 x-2/5x=120 4x+18x=132
60%x+0.4x=120
120=-2x+60x+800